2021
DOI: 10.18051/jbiomedkes.2021.v4.130-138
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan obat tradisional di Indonesia: distribusi dan faktor demografis yang berpengaruh

Abstract: Indonesia merupakan negara yang kaya akan sumber alam dan memiliki lebih dari 400 etnis dan sub etnis yang tersebar di seluruh wilayah Indonesia. Daerah Jawa, Sunda, Manado, Kalimantan, dan berbagai daerah lainnya masih memanfaatkan tanaman sebagai obat tradisional yang merupakan warisan turun temurun. Menurut Badan Pengawas Obat dan Makanan  obat tradisional dibagi menjadi 3 kategori, dan digunakan oleh masyarakat secara turun temurun, dengan cara pengolahan yang sederhana.  Secara global, rata–rata penggunaa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
18

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
1
12
0
18
Order By: Relevance
“…This study revealed that most patients with diabetes mellitus self-medicated with herbal remedies and antidiabetic drugs. This finding supports the conclusion of a previous study that self-medication with traditional medicines increased from 15.2% to 38.3% (Adiyasa and Meiyanti, 2021). However, healthcare professionals must be consulted prior to combining herbal and prescription medications to prevent potential medication errors (Hayyu et al, 2022).…”
Section: Disscussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study revealed that most patients with diabetes mellitus self-medicated with herbal remedies and antidiabetic drugs. This finding supports the conclusion of a previous study that self-medication with traditional medicines increased from 15.2% to 38.3% (Adiyasa and Meiyanti, 2021). However, healthcare professionals must be consulted prior to combining herbal and prescription medications to prevent potential medication errors (Hayyu et al, 2022).…”
Section: Disscussionsupporting
confidence: 86%
“…Most individuals believe that herbal medicines have no side effects, which has led to a rise in their use as an alternative to conventional medicine (Lau and Sunarti, 2018). Globally, the average use of traditional medicine is around 20-28% (Adiyasa and Meiyanti, 2021). Based on Riset Kesehatan Dasar (RISKESDAS), conducted by Ministry of Health, Indonesia, 59.12% of Indonesian households still consume herbal medicine (Ministry of Health, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nilai budaya yang tinggi di masyarakat dipengaruhi oleh lingkungan sekitar dan kebiasaan atau tradisi masyarakat yang sudah ada serta terbukti secara empiris sehingga menjadi kebiasaan di desa tersebut, hal ini sesuai dengan teori bahwa budaya untuk mengkategorikan dan mengklasifikasi pengalaman (Adiyasa & Meiyanti, 2021). Budaya yang lahir ditengah masyarakat biasanya terlahir dari dorongan lokal yang secara rohani dan material pentong bagi kehisupan sosial suatu lingkungan masyarakat.…”
Section: Pembahasanunclassified
“…Along with the development of plant-based herbal medicine as a community-based alternative treatment, research on plants with antifungal properties is required. Because, aside from being inexpensive and employing traditional medicine, it rarely possesses side effects (Adiyasa & Meiyanti, 2021).…”
Section: Introductionmentioning
confidence: 99%